Multicenter review of a tadalafil suspension formulation in infants and children with pulmonary hypertension: a north american experience. (25th January 2023) - Youssef, D; Handler, S; Richards, S; Sheppard, C; Smith, J; Tillman, K; Pietrosanu, M; Kirkpatrick, E; Bates, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Pulmonary arterial hypertension (PAH) is a disease characterised by an increase in pulmonary vascular resistance and pulmonary artery pressure. Phosphodiesterase type 5 (PDE5) inhibitors, with sildenafil the earliest among them, are widely used in the management of pediatric PAH. There has more recently been a transition to once-daily tadalafil suspensions. Herein, we present a multicenter experience detailing safety, tolerability and haemodynamic data utilizing tadalafil suspension alone or in combination for the management of pediatric PAH. Methods and materials: We performed a retrospective review of all infants and children at two North American paediatric PH centres between December 2013 and April 2022. We included all patients less than 9 years of age who were treated with a tadalafil suspension after an initial treatment with sildenafil. Demographic, clinical, imaging, and laboratory data were collected. Results: Over the study period, 158 children were treated with tadalafil therapy: 41 (25.9%) had group 1 PAH, 81 (51.3%) had group 3 PH, and 33 (20.9%) had group 5 PH. The median initial dose of tadalafil was 1.0 mg/kg once daily with a median time to maximum dose of 1 day. The majority of patients required the suspension formulation due to an inability to take oral tablets or the need for nasogastric or nasojejunal feeding. We observed improvements in median echocardiographic parameters in the six months following initiation, namely, in RVFAC from 34.7% (Q1 = 31.0%, Q3 = 42.0%) to 37.0% (Q1 = 31.0%, Q3 = 44.0%) and in TAPSE from 1.0 (Q1 = 0.8, Q3 = 1.7) cm to 1.3 (Q1 = 1.0, Q3 = 1.7) cm. We observed median decreases in RVSp from 51.0 (Q1 = 35.0, Q3 = 69.0) mmHg to 37.0 (Q1 = 30.0, Q3 = 50.0) mmHg and in NT pro BNP levels from 439.0 (Q1 = 217.0, Q3 = 2051.0) ng/L to 313.0 (Q1 = 193.0, Q3 = 1110.0) ng/L. Tadalafil therapy was well tolerated over the six-month period: at baseline, only four patients (2.5%) reported gastrointestinal side effects, two (1.3%) reported adverse skin adverse effects (i.e., rash and flushing), and one (0.6%) reported adverse neurological effects. At six months, 150 patients (94.9%) reported no adverse effects. Conclusion: Tadalafil, a long-acting PDE5 inhibitor, when administered in a suspension formulation, has a safe and tolerable adverse effect profile once patients are established on sildenafil therapy. Following 6 months of once daily tadalafil suspension, alone or in combination, showed a trend towards improvement in clinical parameters, echocardiographic measurements, and laboratory results for pediatric PAH. All patient adverse effects were managed with non pharmacological measures and there was good patient compliance.